Degradation of PVDF-Coated Fabrics after Engineering Applications: Correlations between Surface Microstructure, Physical Properties, and Mechanical Properties Based on Statistical Analysis - Yingying Shang; Bin Yang; Minger Wu; Youji Tao; Jiaxiang Qin (Advances in Polymer Technology)
Material degradation has marked impact on the long-term properties and service life of membrane structures. This study is aimed at assessing and understanding the deterioration in visual aspect, surface microstructure, and mechanical properties of a polyvinylidene fluoride (PVDF) polymer after engineering applications. Three groups of PVDF-coated fabrics were removed from different membrane structures in China, which have been used for 15, 16, and 19 years, respectively. Firstly, spectrocolorimetry tests were carried out to determine the evolution of chromaticity and lightness. Other methods such as contact angle and thickness measurements were used to characterize the physical properties. Then, surface morphology was observed by using scanning electron microscope (SEM) technology. Moreover, a series of uniaxial tensile tests and tearing tests were performed to obtain the mechanical indicators including uniaxial tensile strength, strain at break, tearing strength, and uniaxial elastic modulus. In order to further study the degradation mechanism, infrared spectroscopy was used to characterize the molecular structure of aged fabrics. Finally, Principal Component Analysis (PCA) provided a comprehensive description of correlations between surface microstructure, physical properties, and mechanical properties. This paper offers a further understanding of the design, qualification, and durability evaluation of membrane structures.